Deskripsi Tingkat Kemampuan Menyelesaikan Soal Cerita Matematika Siswa Kelas VI SD Negeri Kecamatan Tanete Riattang Kabupaten Bone - syamsuddin syamsuddin; makmur nurdin; abd kadir (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2018)
This study aims to describe the level of language transfer ability, computational ability, and the ability to solve mathematical story problems, grade VI students of SD Negeri Kecamatan Tanete Riattang, Bone Regency. This type of research is ex-post facto which is descriptive in nature. The population of this study were all sixth grade students of SD Negeri Tanete Riattang District, Bone Regency, as many as 1006 students scattered in 31 schools. Sampling was carried out by using 99 stratified cluster random sampling techniques. The instrument used in this study is a multiple choice test of math story questions which are packaged in three forms of multiple choice questions, each consisting of 20 items. Data analysis techniques used are descriptive statistics with frequency distribution techniques, average counts and percentages. The results of this study indicate that: (1) The level of language transfer ability is in the very low category with an average value of 31.30; (2) The level of computing ability is in the very low category with an average value of 32.40; (3) The ability to solve math story problems is in the very low category with an average value of 27.27; (4) The level of synchronization of answers between types of tests students are also classified in the very low category, which is an average of 27.88%. This can mean that the correctness of students' answers in one particular test question is not necessarily in sync with other types of test questions. Thus, most students in answering test questions with guesses without understanding the nature of the three tests as a whole and inseparable unity.